Guiding principles for the interaction between academic programs in audiology and industry. - Windmill IM; Freeman BA; Jerger J; Scott JM (Audiology Today)
Neither academic programs nor industry are bond by the same ethical framework as members of a professional organization. The purpose of this document is to propose guidelines that could be voluntarily adopted by academic programs and industry.